PENERAPAN MODEL SAVI DALAM PEMBELAJARAN MENULIS CERPEN PADA SISWA - Chairul Bachri Siregar (Universitas Negeri Medan, 2015)
This research is motivated by shortcomings in writing short stories inparticular students to write short stories opposite of events that never happened.It was influenced by the uses of the learning model. The author provides analternative model of SAVI for use in teaching writing. However, previous authorswill test the SAVI models to determine the level of effectiveness. Based on theresearch background, this study refers to some formulation of the problem,namely: 1) How is the ability of class IX students of SMP Negeri 6 Bahorok inlearning to write short stories before and after the SAVI models applied in theexperimental class; 2) How is the ability of class IX students of SMP Negeri 6Bahorok in learning to write short stories without using SAVI models in thecontrol class; 3) Is there a significant difference between the ability to writepoetry class IX students of SMP Negeri 6 Bahorok in the experimental class in thecontrol class. The purpose of this study is to describe things that are listed in theformulation of the problem.The underlying theory is a theoretical model of SAVI